Futsal Shooting Skill Level and Dominant Physical Condition in Extracurricular Activities of State Middle School 1 Batu Sopang, Paser Regency, East Kalimantan - Ahmad Hidayat; Ramadhan Arifin; Mita Erliana (Universitas Negeri Semarang, 2025)
This study aims to determine the level of futsal shooting skills and dominant physical conditions of extracurricular participants at State Middle School 1 Batu Sopang, Paser Regency, East Kalimantan. The method used is descriptive quantitative with a futsal shooting skills measurement test and a dominant physical condition test of futsal extracurricular participants at State Middle School 1 Batu Sopang, Paser Regency, East Kalimantan. The results of the study showed that most participants had a shooting skill level in the enough category, which was 10 people (80%), and a good category of 2 people (20%). The results of the overall physical condition test were in the enough category (with a conversion value of 6). The conclusion of the results of the study of the level of futsal shooting skills and dominant physical conditions of extracurricular participants at Middle School Negeri 1 Batu Sopang, Paser Regency, East Kalimantan, the average shooting skill level was enough and the results of the physical condition test were in the enough category.